PENDAMPINGAN PEMBUATAN QRIS SEBAGAI SISTEM PEMBAYARAN KEWIRAUSAHAAN UMKM KERIPIK TEMPE CHATENORI - Muhammad Ihsan Halim Harahap; Tomi Candra Wijaya; Netasia Putri Ria; Lala Aprianingsih (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Micro, small, and medium enterprises (UMKM) make a significant contribution to the Indonesian economy, but they still face various challenges, particularly in payment systems. This study aims to examine the implementation of a digital payment system to increase the competitiveness of the Chatenori Tempe Chips UMKM. The method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation